Human Resource Management Practices and Employee Retention - Prakash Shrestha; Dhan Krishna Prajapati (Journal of Balkumari College, 2023)
The purpose of this study is to examine the relationship between HRM practices and employee retention in bank and financial institutions (BFIs) of Nepal. Recruitment and selection, training and development, promotion opportunities, and compensation practices are the four HRM practices examined in this study. A questionnaire with a five-point Likert scale is used for collecting data. 135 completed questionnaires were returned out of the 205 that were distributed, representing a 65.85% response rate. The results show that selection and recruitment have no significant relationship with employee retention. The findings also indicate that there is little to no relationship between training and development and employee retention. There is a strong positive association between employee retention and other aspects of HRM practices like promotion opportunities and compensation practices. Therefore, Nepalese BFIs need to provide timely promotion opportunities and fair compensation practices so that they can retain talented employees in their organizations. Moreover, to meet the challenge of gaining a competitive edge, today’s organizations must create a workplace that encourages performance, productivity, and retention.